2021
DOI: 10.1177/03010066211055983
|View full text |Cite
|
Sign up to set email alerts
|

“There Is No (Where a) Face Like Home”: Recognition and Appraisal Responses to Masked Facial Dialects of Emotion in Four Different National Cultures

Abstract: The theory of universal emotions suggests that certain emotions such as fear, anger, disgust, sadness, surprise and happiness can be encountered cross-culturally. These emotions are expressed using specific facial movements that enable human communication. More recently, theoretical and empirical models have been used to propose that universal emotions could be expressed via discretely different facial movements in different cultures due to the non-convergent social evolution that takes place in different geog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 79 publications
3
21
0
Order By: Relevance
“…& Ansorge, 2017). Our lab has also replicated these findings in several previous designs and publications Tsikandilakis, Chapman & Pierce, 2018;Tsikandilakis, Bali, Derrfuss & Chapman, 2019;Tsikandilakis et al, 2020;Tsikandilakis et al, 2021a;2021b; see Figure 1; see also Appendix 1a & 1b). To address the important issue that different individuals and stimulus types require different signal strengths for the duration of their presentation for accomplishing subliminality, we introduced, in our experimental designs, a stage during which we calculated the durations of presentation that provided Bayesian evidence (Dienes, 2014) for unbiased (Zhang & Mueller, 2005) chance-level performance (Erdelyi, 2004) in response to masked cues.…”
Section: Individual Consciousness and Unconsciousnesssupporting
confidence: 82%
“…& Ansorge, 2017). Our lab has also replicated these findings in several previous designs and publications Tsikandilakis, Chapman & Pierce, 2018;Tsikandilakis, Bali, Derrfuss & Chapman, 2019;Tsikandilakis et al, 2020;Tsikandilakis et al, 2021a;2021b; see Figure 1; see also Appendix 1a & 1b). To address the important issue that different individuals and stimulus types require different signal strengths for the duration of their presentation for accomplishing subliminality, we introduced, in our experimental designs, a stage during which we calculated the durations of presentation that provided Bayesian evidence (Dienes, 2014) for unbiased (Zhang & Mueller, 2005) chance-level performance (Erdelyi, 2004) in response to masked cues.…”
Section: Individual Consciousness and Unconsciousnesssupporting
confidence: 82%
“…In the area of moral processing the development of set and acknowledged image databases for presenting moral and, particularly, immoral image stimuli (Crone, Bode, Murawski & Laham, 2018) is not sufficiently developed (see McCullough & Willoughby, 2009; see also Shariff et al, 2016). Experimental research in this areaas also in other relevant areas of psychology (see, for example, Axelrod, Bar & Rees, 2015) would either have to go to the length of creating a relevant dataset (see, for example, Clifford, Iyengar, Cabeza & Sinnott-Armstrong, 2015;Tsikandilakis et al, 2021b;in press) or thoroughly and reliably validate a subcategory of images from an existing database (see, for example, Harenski, Antonenko, Shane & Kiehl, 2010;. This hurdle is particularly important because both traditional (see, for example, Freedberg, 1989) and more contemporary (see, for example, Warren, 2009) psychological research has shown that images are potent elicitors for the activation of neural structures such as the amygdala, and the cingulate and insular cortices that are associated with automatic processing and peripheral nervous system arousal (Brooks et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, we should note that the results of the present study cannot rule out the possibility that the nonverbal dialects have also affected the recognition of microexpressions since we had also found the ingroup disadvantage under racial group situations (in Study 1A and 1B) in which the nonverbal dialect differences were not controlled. Researchers need to recruit participants from more diverse culture backgrounds (e.g., White participants) and employ instructed emotional faces (e.g., Tsikandilakis et al, 2021) to explore this issue in the future. Contrary to the universal tendency of ingroup favoritism found across cultures (e.g., Tajfel et al, 1971;Hewstone et al, 2002;Ji et al, 2019;Makhanova et al, 2022), a counterintuitive phenomenon of ingroup derogation (i.e., the tendency to favor members of one's outgroup over members of one's ingroup) has also been reported (mainly in the East Asian cultures; Ma-Kellams et al, 2011;Zhao et al, 2012;Wu et al, 2015Wu et al, , 2016bWu et al, , 2019.…”
Section: Discussionmentioning
confidence: 99%